2014
DOI: 10.1002/dmrr.2576
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of acarbose in different geographical regions of the world: analysis of a real‐life database

Abstract: This study is from the Acarbose pooled Database Integrated Analysis-NonInterventional Studies (AcarDIA-NIS) project. AbstractBackground Alpha-glucosidase inhibitors are recommended in some international guidelines as first-line, second-line and third-line treatment options but are not used worldwide due to perceived greater effectiveness in Asians than Caucasians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 56 publications
0
26
0
Order By: Relevance
“…Furthermore, although the SGLT2 inhibitors dapagliflozin, canagliflozin and empagliflozin do not increase the risk of hypoglycaemia, there is evidence that they increase the risk of hypovolemic side‐effects and that their glycaemic efficacy is diminished in moderate‐to‐severe renal impairment . In addition, alpha glucosidase inhibitors are not generally recommended for people with renal impairment due to potential accumulation and lack of safety information …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, although the SGLT2 inhibitors dapagliflozin, canagliflozin and empagliflozin do not increase the risk of hypoglycaemia, there is evidence that they increase the risk of hypovolemic side‐effects and that their glycaemic efficacy is diminished in moderate‐to‐severe renal impairment . In addition, alpha glucosidase inhibitors are not generally recommended for people with renal impairment due to potential accumulation and lack of safety information …”
Section: Discussionmentioning
confidence: 99%
“…28 In addition, alpha glucosidase inhibitors are not generally recommended for people with renal impairment because of potential accumulation and lack of safety information. 28,29 The ADA/EASD treatment guidelines have designated GLP-1…”
Section: Discussionmentioning
confidence: 99%
“…To date, there are no evidences to suggest different treatment strategies for LADA in Asian and European people. However, it is hypothesised that due to differences in ethnicity, lifestyle, and eating habits, efficacy of any particular treatment in LADA may differ between 2 populations in a similar way as in Asian DM2 patients in whom incretin‐based therapies and alpha‐glucosidase inhibitors show better efficacy than in Caucasians …”
Section: Treatment Strategiesmentioning
confidence: 97%
“…However, it is hypothesised that due to differences in ethnicity, lifestyle, and eating habits, efficacy of any particular treatment in LADA may differ between 2 populations in a similar way as in Asian DM2 patients in whom incretin-based therapies and alpha-glucosidase inhibitors show better efficacy than in Caucasians. 104,105 A pilot trial using rosiglitazone plus insulin in Chinese Asians showed preserved β-cell function as compared to Insulin alone. 106 Interestingly, Chinese herb extract tripterygium an oral immunosuppressive agent maintained stimulated C-peptide levels in Chinese LADA subjects.…”
Section: Differencesmentioning
confidence: 99%
“…The effects of both drugs in reducing HbA1c were similar regardless of the patients' body mass index (BMI) 12 . Because certain populations may respond more favorably to either acarbose 13 or metformin, the present post-hoc analysis was undertaken to identify the characteristics of participants in the MARCH trial at baseline and in the treatment period that may be associated with greater efficacy in achieving a HbA1c level <7% (<53 mmol/mol). These J U S T A C C E P T E D results may help inform treatment decisions with respect to initiation of antidiabetic treatment, offering a patient-centered approach to the management of type 2 diabetes 2 .…”
Section: Introductionmentioning
confidence: 99%